HUBUNGAN ANTARA ANEMIA DAN LUARAN PERSALINAN PADA IBU HAMIL YANG MENGGUNAKAN KELAMBU BERINSEKTISIDA DAN TIDAK MENGGUNAKAN KELAMBU BERINSEKTISIDA DI DAERAH ENDEMIS MALARIA VIVAX - Nugraheni, Diah Eka (JURNAL MEDIA KESEHATAN, 2012)
This study aims to determine the relationship between the use of insecticide-treated nets on anemia and birth outcome in vivax malaria-endemic areas. This study uses a retrospective cohort analysis design with a sample of 138 people. Subjects were divided two groups: the group that during pregnancy using insecticide-treated nets (n = 69) and those who do not use insecticide-treated nets (n = 69). Hemoglobin level examination conducted in the laboratory clinic, gestational age calculated from LMP mother, birth weight using the recording of documentation by a midwife birth helper. The use of insecticide-treated nets on anemia associated with the negative correlation at the level of mild correlation (p = 0.003, OR 95% CI = 3.31, r = -0505). The use of insecticide-treated nets against preterm labor associated with the negative correlation at the level of a weak correlation (p = 0015. OR 95% CI = 4.14, r = -0207), whereas the variable abortion, low birth weight and IUFD there were no significant differences. Increased risk of anemia and 3:31 times greater risk of preterm delivery increased 4:14 times larger than the group of pregnant women using insecticide-treated nets. Conclusions of this study is the use of insecticide treated bed nets during pregnancy can reduce the risk of anemia and premature labor in pregnant women in vivax malaria-endemic areas